Teachers Questions in Reading Classes - Zuliati Rohmah (TEFLIN, 2002)
Abstract: The present paper discusses an English teachers questions in Reading classes at MAN Malang III. Types of questions, functions of teachers questions, question levels and the strategies applied by the teacher were put as the research problems. Non-participant observaÃÂtion was applied to collect the data with the researcher as the main inÃÂstrument aided by field-notes and a tape recorder. It was found that the distribution of the questions did not allow the students to talk longer and to think more analytically. Meanwhile, the strategies applied by the teacher helped the students to respond to the questions previously unanswered. The teacher is suggested to produce more open and referÃÂential question as well as inference and evaluation questions as to give more chances for the students to think aloud more.